2014
DOI: 10.1016/j.pain.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Nox2-dependent signaling between macrophages and sensory neurons contributes to neuropathic pain hypersensitivity

Abstract: Emerging lines of evidence indicate that production of reactive oxygen species (ROS) at distinct sites of the nociceptive system contributes to the processing of neuropathic pain. However, the mechanisms underlying ROS production during neuropathic pain processing are not fully understood. We here detected the ROS-generating nicotinamide adenine dinucleotide phosphate oxidase isoform Nox2 in macrophages of dorsal root ganglia (DRG) in mice. In response to peripheral nerve injury, Nox2-positive macrophages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 67 publications
3
54
1
Order By: Relevance
“…ROS generated in the spinal cord following nerve injury lead to sensitization of dorsal horn neurons via phosphorylation of N-methyl-D-aspartate (NMDA) and AMPA receptors (Gao et al, 2007; Kim et al, 2011) and through a loss of GABA A neurons (Yowtak et al, 2013). ROS generated in the periphery are also critically involved in hyperalgesia following nerve injury or inflammation (Wang et al, 2008; Linley et al, 2012; Kallenborn-Gerhardt et al, 2014). However, there is limited information available on changes in ROS levels within either DRG or TG following peripheral injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS generated in the spinal cord following nerve injury lead to sensitization of dorsal horn neurons via phosphorylation of N-methyl-D-aspartate (NMDA) and AMPA receptors (Gao et al, 2007; Kim et al, 2011) and through a loss of GABA A neurons (Yowtak et al, 2013). ROS generated in the periphery are also critically involved in hyperalgesia following nerve injury or inflammation (Wang et al, 2008; Linley et al, 2012; Kallenborn-Gerhardt et al, 2014). However, there is limited information available on changes in ROS levels within either DRG or TG following peripheral injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that excess ROS generated in peripheral tissues and within the spinal cord following nerve injury or inflammation lead to pathological pain conditions (Gao et al, 2007; Wang et al, 2008; Kallenborn-Gerhardt et al, 2014). Recent studies indicate that ROS generated within sensory ganglia, such as dorsal root ganglia (DRG), regulate hypertension by altering the level of neuropeptides (Chapleau, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, experimental evidence shows that nicotinamide adenine dinucleotide phosphate oxidase 2 (Nox2)-positive macrophages are infiltrated into DRG after sciatic nerve injury and are involved in neuropathic pain hypersensitivity, which is impaired in Nox2-deficient mice [50], suggesting that Nox2 regulates peripheral nerve sensory function after injury by targeting macrophages. Collagen VI-deficient mice exhibit a delayed peripheral nerve regeneration by impairing macrophage function, which is rescued by transplantation of wild-type bone marrow cells [21].…”
Section: Role Of Macrophages In Peripheral Nerve Regenerationmentioning
confidence: 99%
“…Further studies are needed to confirm this conclusion using Nox2 or collagen VI conditional knockout mice or treatment strategies specifically targeting macrophages. In addition, pharmacological treatments also support the concept that macrophage is a promising target for improving PNS regeneration [21, 47,50]. For example, oxidized galectin-1 (GAL-1/Ox) is produced by Schwann cells and injured axons that specifically binds to and stimulates macrophages to produce axonal growth-promoting factor, thus promoting axonal regeneration, a process that is blocked by galectin-1 neutralizing antibodies [47].…”
Section: Role Of Macrophages In Peripheral Nerve Regenerationmentioning
confidence: 99%
“…2). In contrast, another study showed that NOX1 mRNA failed to upregulate in the DRG following peripheral nerve injury (PNI) [20]. These results indicate that DRG NOX1 may have a preferential role in inflammatory versus neuropathic pain.…”
Section: Production Of Nitroxidative Species By Neurons Glia and Immentioning
confidence: 99%